SYNTHESIS AND PERFORMANCE TEST OF CO-EEGDMA AS A CARRIER IN PHENOL TRANSPORT USING POLYMER INCLUSION MEMBRANE - Agung Abadi Kiswandono (Jurnal Penelitian Saintek, 2017)
This study was aimed to synthesize the polymer as a carrier, i.e. copolymer (Eugenol-ethylene glycol dimethacrylate, EGDMA) or co-EEGDMA. The synthesis involving eugenol and EGDMA as a crosslinking agent was performed by polymerization using a boron trifl uoro diethyl ether catalyst. The synthesized polymer was then characterized using FTIR, SEM and H-NMR. Co-EEGDMA and two other compounds, namely polyvinyl chloride (PVC) and dibenzyl ether (DBE) as the components in the membrane making process were tested to be used for phenol transport. The components then were tested using Polymer Inclusion Membrane (PIM) method. The characterization results of co-EEGDMA show that eugenol polymerization using EGDMA crosslinking agent has been successfully synthesized. The results also show that the membrane containing the new compounds can be used for phenol transport in multiple times.